Hubungan Pengetahuan dan Sikap Ibu Nifas terhadap Praktik Pemenuhan Kebutuhan Dasar Masa Nifas - Umaroh Umaroh; Suparmi Suparmi; Syamsulhuda Budi Musthofa (Universitas Faletehan, 2024)
During postpartum period, woman's body experiences significant hormonal, physical and emotional changes. There are 3 types of basic needs that must be met during this period, including activity needs, rest needs and nutritional needs This research aimed to determine the relationship between knowledge and attitudes with basic needs fulfilments during postpartum period. This research used a cross-sectional approach. The population was all normal postpartum mothers in Public Health Centers and Independent Midwife Practices in Semarang City and around. However, this study selected 30 postpartum mothers as the respondents by simple random sampling technique. The research findings showed the most significant relationship were attitude-rest practices and knowledge-nutritional practices which the p-value was 0.001. The p value of knowledge-rest practices relationship was 0.002, attitude-activity practices 0.003, attitude-nutritional practices 0.028, and knowledge-activity practices 0.035. Postpartum mothers should understand more about their basic needs; thus, all their basic needs can be fulfilled well.